(untitled) (Al-Qamar, 2023)
The Islamic tradition of thought is grounded in a rich body of knowledge that has been developed over centuries, derived from the revealed wisdom of Qur’an & that of the Sunnah (prophetic practices) of the Prophet (PBUH). This knowledge encompasses a broad range of fields, including theology, jurisprudence, ethics, and spirituality, among others. This paper examines the original sources of Islamic thought that have been instrumental in shaping the Islamic intellectual tradition. The paper begins by discussing the Quran, which is the original source of Islamic knowledge, and examines Hadith o Sunnah (sayings and actions) of the Prophet Muhammad and serve as a complementary source of Islamic law and ethics. The paper also explores the role of Ijtihad (deriving guidance from Qur’an & Sunnah through human reason and intellect) in Islamic thought, including the use of logical reasoning and philosophical inquiry to understand Islamic teachings.